Clinically relevant dosing and pharmacokinetics of DNA-encoded antibody therapeutics in a sheep model - Hollevoet, Kevin; Thomas, Debby; Compernolle, Griet; Vermeire, Giles; De Smidt, Elien; De Vleeschauwer, Stéphanie; Smith, Trevor R. F.; Fisher, Paul D.; Dewilde, Maarten; Geukens, Nick; Declerck, Paul (Frontiers in Oncology, 2022)
DNA-encoded delivery and in vivo expression of antibody therapeutics presents an innovative alternative to conventional protein production and administration, including for cancer treatment. To support clinical translation, we evaluated this approach in 18 40-45 kg sheep, using a clinical-matched intramuscular electroporation (IM EP) and hyaluronidase-plasmid DNA (pDNA) coformulation setup. Two cohorts of eight sheep received either 1 or 4 mg pDNA encoding an ovine anti-cancer embryonic antigen (CEA) monoclonal antibody (mAb; OVAC). Results showed a dose-response with average maximum serum concentrations of respectively 0.3 and 0.7 µg/ml OVAC, 4-6 weeks after IM EP. OVAC was detected in all 16 sheep throughout the 6-week follow-up, and no anti-OVAC antibodies were observed. Another, more exploratory, cohort of two sheep received a 12 mg pOVAC dose. Both animals displayed a similar dose-dependent mAb increase and expression profile in the first two weeks. However, in one animal, an anti-OVAC antibody response led to loss of mAb detection four weeks after IM EP. In the other animal, no anti-drug antibodies were observed. Serum OVAC concentrations peaked at 4.9 µg/ml 6 weeks after IM EP, after which levels gradually decreased but remained detectable around 0.2 to 0.3 µg/ml throughout a 13-month follow-up. In conclusion, using a delivery protocol that is currently employed in clinical Phase 1 studies of DNA-based antibodies, we achieved robust and prolonged in vivo production of anti-cancer DNA-encoded antibody therapeutics in sheep. The learnings from this large-animal model regarding the impact of pDNA dose and host immune response on the expressed mAb pharmacokinetics can contribute to advancing clinical translation.